A Systemic Functional Approach to the Categorial Status of Post-Nominal Monosyllabic Localizers in Mandarin Chinese - He, Wei (SAGE open, 2025)
Literature entails six viewpoints regarding the categorial status of post-nominal monosyllabic localizers in Mandarin Chinese, including locative particles, nouns or a subclass of nominals, clitics, spatial enclitics or particles, postpositions and postpositions in circumpositions. In order to resolve the disputes, this article argues for the postposition viewpoint from a systemic functional perspective given limited studies regarding this in the literature. Systemic Functional Linguistics can provide proper descriptions for various linguistic phenomena, including localizers, observing the function-oriented language study principle. Hence, to specify the categorial status of post-nominal monosyllabic localizers, this study takes a systemic functional approach to investigate their semantic and syntactic functions. The findings indicate that post-nominal monosyllabic localizers are postpositions, for like prepositions, they express positional relationships between things, and along with their preceding nominals, can function as Subjects, Complements and Adjuncts within Chinese clauses, and as completives in Chinese prepositional phrases.